Cytokine Patterns in Maternal Serum From First Trimester to Term and Beyond - Jarmund, Anders Hagen; Giskeødegård, Guro Fanneløb; Ryssdal, Mariell; Steinkjer, Bjørg; Stokkeland, Live Marie Tobiesen; Madssen, Torfinn Støve; Stafne, Signe Nilssen; Stridsklev, Solhild; Moholdt, Trine; Heimstad, Runa; Vanky, Eszter; Iversen, Ann-Charlotte (Frontiers in Immunology, 2021)
Pregnancy implies delicate immunological balance between two individuals, with constant changes and adaptions in response to maternal capacity and fetal demands. We performed cytokine profiling of 1149 longitudinal serum samples from 707 pregnant women to map immunological changes from first trimester to term and beyond. The serum levels of 22 cytokines and C-reactive protein (CRP) followed diverse but characteristic trajectories throughout pregnancy, consistent with staged immunological adaptions. Eotaxin showed a particularly robust decrease throughout pregnancy. A strong surge in cytokine levels developed when pregnancies progressed beyond term and the increase was amplified as labor approached. Maternal obesity, smoking and pregnancies with large fetuses showed sustained increase in distinct cytokines throughout pregnancy. Multiparous women had increased cytokine levels in the first trimester compared to nulliparous women with higher cytokine levels in the third trimester. Fetal sex affected first trimester cytokine levels with increased levels in pregnancies with a female fetus. These findings unravel important immunological dynamics of pregnancy, demonstrate how both maternal and fetal factors influence maternal systemic cytokines, and serve as a comprehensive reference for cytokine profiles in normal pregnancies.